Prescriptive standards of echocardiographic morphometric and functional parameters in uncomplicated monochorionic diamniotic fetuses. (8th July 2021) - Torres, Ximena; Martínez, Josep M.; Gómez, Olga; MartÍnez‐Portilla, Raigam J.; García‐Otero, Laura; Crispi, Fátima; Masoller, Narcís; Sepúlveda‐Martínez, Álvaro; Marimón, Edda; Gratacós, Eduard; Figueras, Francesc; Bennasar, Mar
Abstract: Objective: To create prescriptive standards of cardiac morphometric and functional parameters in a cohort of uncomplicated monochorionic diamniotic (MCDA) twins. Method: Fetal echocardiography was performed in a cohort of uncomplicated monochorionic twin fetuses scanned longitudinally, including comprehensive morphometric and functional parameters, using 2‐D imaging, M‐mode and conventional Doppler. A multilevel polynomial hierarchical model adjusted by gestational age and estimated fetal weight was used to fit each cardiac parameter. Results: The global heart dimensions including the atrial and ventricular areas, the ventricles dimensions and myocardial wall thicknesses and most of the functional parameters, such as the longitudinal myocardial motion and the biventricular cardiac output showed a positive quadratic increment throughout pregnancy. On the other hand, the left ejection fraction, shortening fraction and right fractional area change decreased with gestational age. Scatterplots for the main structural and functional parameters and ratios by gestational age, with mean, 5th, 10th, 90th, and 95th percentiles are provided. Regression equations by estimated fetal weight are also created. Conclusion: We provide specific comprehensive echocardiographic prescriptive standards for uncomplicated MCDA twin fetuses following current standardized methodology. The implementation of these charts will potentially help to better identify abnormal cardiovascular parameters associated to monochorionic complications. Key points: What's already known about this topic? Despite presenting normal cardiac morphometry and function, uncomplicated monochorionic diamniotic twin fetuses showed signs of cardiac adaptation to volume/pressure overload when compared to low‐risk singletons, as a response to the unique monochorionic placental vascular anastomoses. Reference charts for some functional echocardiographic parameters have already been published in monochorionic twins, however nomograms for most of the current validated morphometric and functional echocardiographic parameters are still lacking. What does this study add? This work provides morphometric and functional echocardiographic prescriptive standards based on a cohort of 110 uncomplicated monochorionic diamniotic twin fetuses from 16 to 34 weeks of gestation, evaluated by experienced specialists in fetal echocardiography following the current standardized methodology. The implementation of these charts will potentially help to better identify abnormal cardiovascular parameters associated to monochorionic diamniotic twins' complications, optimizing the available therapeutic interventions.